1990
DOI: 10.1007/bf01310622
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA for detection of antibodies against influenza A nucleoprotein in humans and various animal species

Abstract: A double antibody sandwich blocking ELISA, using a monoclonal antibody (MAb) against influenza A nucleoprotein (NP) was developed to detect antibodies against influenza. Collections of serum samples were obtained from human and various animal species. All influenza A subtypes induced antibodies against hemagglutinins and NP. A close correlation between titers of the hemagglutination inhibition (HI) test and the NP-ELISA was seen. Antibodies against influenza NP were demonstrated in serum samples from humans, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 27 publications
3
75
0
3
Order By: Relevance
“…Forty-six of 1,095 samples of ''seals and sea lions'' from the North and Bering Seas had antibodies to influenza A as determined by ELISA. Further testing revealed exposure to H1, H3, H4, H7 and H12 subtypes (de Boer et al, 1990). One of 32 ringed seal (Phoca hispida) samples from Alaska gave a positive result for influenza antibodies of the H3 and H7 subtypes (Danner and McGregor, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-six of 1,095 samples of ''seals and sea lions'' from the North and Bering Seas had antibodies to influenza A as determined by ELISA. Further testing revealed exposure to H1, H3, H4, H7 and H12 subtypes (de Boer et al, 1990). One of 32 ringed seal (Phoca hispida) samples from Alaska gave a positive result for influenza antibodies of the H3 and H7 subtypes (Danner and McGregor, 1998).…”
mentioning
confidence: 99%
“…Both species were sampled from populations in the Barents Sea in 1991-92 (Steuen et al, 1994). Seroprevalence of influenza A in ''seals and sea lions'' from the North and Bering Seas of 0.4% and 12.7% has also been reported (de Boer et al, 1990).…”
mentioning
confidence: 99%
“…H3 subtypes of influenza A virus have been isolated from dead harbor seals from Cape Cod, U.S.A. [2]. Antibodies to the H3 subtype were detected in the seals from the Bering Sea [6]. H3 subtypes commonly infect other species including humans, pigs, horses and birds [25,32].…”
Section: Discussionmentioning
confidence: 99%
“…All of these seal viruses were of avian origin [2,10,16,35]. Serological investigation of seals in the Bering Sea [6], Barents Sea [30], Alaska [5], Arctic Canada [22], Caspian Sea [24], Lake Baikal and Kara Sea [23] revealed viral infections.…”
mentioning
confidence: 99%
“…In pinnipeds, antibodies against influenza A virus were detected in sera from harp seals (Phoca groenlandica) and hooded seals (Cystophora cristata) collected between 1991 and 1992 in the Barents Sea (Steuen et al, 1994), as well as from sea lions (Otariidae) and seals in the North and Bering seas (De Boer et al, 1990), and a ringed seal (Pusa hispida) in Alaska (Danner et al, 1998). A serological survey of influenza A antibodies from five species of marine mammals collected from Arctic Canada between 1984 and 1998, revealed that 2.5% of ringed seals (Phoca hispida) were serologically positive (Nielsen et al, 2001).…”
Section: Evidence Of Influenza Virus Infections In Arctocephalus Austmentioning
confidence: 99%